1999
DOI: 10.1002/(sici)1522-7243(199905/06)14:3<153::aid-bio534>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

The phagocyte chemiluminescence paradox: luminol can act as an inhibitor of neutrophil NADPH-oxidase activity

Abstract: The chemiluminescence system amplified by luminol or isoluminol is a sensitive and widely used method for determination of respiratory burst products generated by the NADPH‐oxidase in phagocytes. The present study shows that luminol, but not isoluminol, can inhibit the release of oxygen metabolites generated by human neutrophil NADPH‐oxidase. The difference in structure between luminol and isoluminol (rendering luminol more lipophilic than isoluminol, and thereby membrane‐permeable), is suggested to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…2, Curve A). In accordance with data in the literature [20], when PMNLs were kept in a reaction mixture containing luminol for 10 min before stimulation , they exhibited a reduced .62 § 20/% ROI production upon fMLP stimulation. Therefore, the points of Curve A in Fig.…”
Section: Lack Of Correlation Between Roi Production and [Ca 2c ] I Sisupporting
confidence: 90%
“…2, Curve A). In accordance with data in the literature [20], when PMNLs were kept in a reaction mixture containing luminol for 10 min before stimulation , they exhibited a reduced .62 § 20/% ROI production upon fMLP stimulation. Therefore, the points of Curve A in Fig.…”
Section: Lack Of Correlation Between Roi Production and [Ca 2c ] I Sisupporting
confidence: 90%
“…For LPO the observation period of 4 h was chosen as we previously, with similar experimental conditions, have found a continuous LPO during 4 h (Wu et al , 1999). As to the oxidative metabolism we dared not extend the observation period beyond 1 h as we have found that not all neutrophils in a population survive several hours in NBT (unpublished data) and as luminol might act as an inhibitor of neutrophil NADPH‐oxidase activity (Fäldt et al , 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Together these findings lead to the following. First, since there was no significant effect of LumH 2 itself on neutrophils in our studies, on inhibition of O 2 À release (Faldt et al, 1999) or on LumH 2 -induced CL (Allred et al, 1980), in the absence of extracellular HRP the LumH 2 -dependent CL signal corresponds to a first approximation to intracellular production of ROS. Therefore, the difference between the two curves presented in Fig.…”
Section: Discussionmentioning
confidence: 63%